Neuroendocrine marker staining pattern categorization of small‐sized pulmonary large cell neuroendocrine carcinoma. Issue 11 (3rd October 2019) - Minami, Kazuhiro; Tanaka, Yugo; Ogawa, Hiroyuki; Jimbo, Naoe; Nishio, Wataru; Yoshimura, Masahiro; Itoh, Tomoo; Maniwa, Yoshimasa
Abstract: Background: The aim of this study was to identify subgroups with good or bad prognosis in patients with pulmonary large cell neuroendocrine carcinoma (LCNEC) based on immunostaining patterns with neuroendocrine markers and compare them with small cell lung carcinoma (SCLC). Methods: From January 2001 to December 2017, of all patients with resected LCNEC and SCLC, we selected patients whose pathological tumor sizes were ≤30 mm in diameter (defined as small‐sized tumors) and who underwent complete resection with lymphadenectomy. We classified patients with small‐sized LCNEC (sLCNEC) into two subgroups based on immunostaining patterns with three neuroendocrine markers (chromogranin A, synaptophysin, and NCAM) and compared them to small‐sized SCLC (sSCLC). Results: A total of 48 patients with sLCNEC and 39 patients with sSCLC were enrolled. Of 48 patients with sLCNEC, 21 were categorized as the small‐sized triple‐positive group (sTP), whose patients were positive for the three neuroendocrine markers, and 27 patients were categorized as the small‐sized nontriple‐positive group (sNTP), whose patients were not positive for all three neuroendocrine markers. The percentage of lymph node metastasis was significantly lower in sNTP than in sTP and sSCLC. There was no significant difference in overall survival, but recurrence‐free survival (RFS) and tumor‐specific survival (TSS) were significantly poorer in sTP and sSCLC than in sNTP. Multivariate analysis revealed sTP and sSCLC were independent prognostic factors for poorer RFS and TSS than those of sNTP. Conclusions: The sNTP subgroup had a good prognosis and the sTP subgroup a poor prognosis. There were some similarities in clinicopathological features between sTP and sSCLC.